2021
DOI: 10.1002/jso.26641
|View full text |Cite
|
Sign up to set email alerts
|

A survey of surgical management of the sentinel node positive melanoma patient in the post‐MSLT2 era

Abstract: Background: The evidence-based management of melanoma patients with a positive sentinel lymph node biopsy (SLNB) has undergone a dramatic shift following publication of practice-changing surgical trials demonstrating no melanoma-specific survival advantage for completion lymph node dissection (CLND) in this scenario.We aimed to survey how surgeons' clinical practice had shifted in response to new evidence from these trials, and at a time when there was starting to become available systemic adjuvant treatments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…But only patients with micrometastases beyond the SLN-which only applies to about 20% of SLN-positive cases-benefit from CLND. In contrast, patients with additional non-SLN micrometastases have worse survival rates, and thus having the knowledge about the status of non-SLN tumor load potentially provides prognostic information [14][15][16][17]. Our data confirm the relatively low number of non-SLN micrometastases detected on CLND in 25.8% of cases.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…But only patients with micrometastases beyond the SLN-which only applies to about 20% of SLN-positive cases-benefit from CLND. In contrast, patients with additional non-SLN micrometastases have worse survival rates, and thus having the knowledge about the status of non-SLN tumor load potentially provides prognostic information [14][15][16][17]. Our data confirm the relatively low number of non-SLN micrometastases detected on CLND in 25.8% of cases.…”
Section: Discussionsupporting
confidence: 70%
“…We did not observe significant differences between both groups for these important prognostic parameters. In a survey from Australia and New Zealand published in 2021, replies were received from respondents in 17 countries [17]. Of these, 97% were familiar with the pivotal clinical trials published by Faries et al [5] and Leiter et al [6] In the survey, 5% of respondents reported routinely recommending CLND and 55% recommend CLND in selected cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In those trials, no improvement in melanoma-specific survival (MSS) from CLND was demonstrated. Surgeons do not perform routine CLND after positive SNLB anymore, and they refer patients to adjuvant systemic treatment [14,15]. Omitting CLND leaves us without precise information on local disease burden.…”
Section: Approach To Adjuvant Melanoma Treatment Inclusion Criteriamentioning
confidence: 99%